A new mode of ammonite preservation – implications for dating of condensed phosphorite deposits. (30th April 2015) - Machalski, Marcin; Olszewska‐Nejbert, Danuta
Abstract : Unusual phosphatic casts of the ammonites Mortoniceras ( Subschloenbachia ) sp. and Stoliczkaia sp. from the upper Albian condensed phosphorite bed at Annopol, Poland, are discussed in terms of their taphonomic history. These specimens are interpreted as 'secondary' external casts of ammonite replicas preserved originally as attachment scars on oyster shells. The following genetic history is suggested for this previously undocumented mode of ammonite preservation: (1) settling of shells of dead ammonites on the seafloor; (2) colonization of these shells by oysters and formation of ammonite replicas on left valves of oysters; (3) dissolution of ammonite shells; (4) reworking and fragmentation of oyster shells; (5) casting of ammonite replicas by phosphatic material; and (6) separation of ammonite casts from oyster shells, either through mechanical disintegration or dissolution of the latter. The specimens studied were formed after dissolution of the ammonite conchs, not prior to this event as in the case of typical ammonite steinkerns (internal moulds). Therefore, they are here referred to as 'pseudo‐steinkerns'. The time interval between loss of the original ammonite shells and the formation of oyster‐mediated pseudo‐steinkerns may be very extensive. Therefore, the pseudo‐steinkerns may potentially mislead in biostratigraphic dating of condensed phosphorite deposits.